Product design styling - Dabbs, Peter, ....- (London : Laurence King Publishing, 2021)
In this, the first product design book devoted purely to styling, Peter Dabbs helps students and professionals to understand how to style their own consumer-focused products. Providing a clear and simple breakdown of the stages in the styling process, Product Design Styling is packed with: Annotated illustrations, Photographs of industry examples, Modified images showing proportions, silhouettes and lines. The clear text and visual examples guide you through a structured professional styling process that has been broken down into digestible stages. Each stage examines and illustrates what designers should be focusing on, how to evaluate what has been designed, and how to then optimize it if required. You will also learn how to analyse and critique the styling of competitors, as well as your own work, and use this awareness to confidently produce superior designs in less time.
Keywords: Product design